The pendulum effect and the commercial businesses of Tulcan and Ipiales: a comparative - Viveros Almeida, Luis Homero (SATHIRI, 2020)
This paper is part of the project called “ Border development Ecuador - Colombia: Province of Carchi - Department of Nariño; Analysis period 2017- 2019”, the purpose of this research was to answer the following questions: How is the pendulum effect of the exchange rate on the commercial business development of the border under study related? In addition, what have been the effects of the commercial policy adopted by the Ecuadorian government in the commercial sector of the border? The research was descriptive, with a quantitative, non-experimental approach, with a sample of 160 participants from Tulcán and Ipiales. The main results indicated that: 61.3% do not perceive negative effects, or directly related to the pendulum exchange effect and 70.6% believe that government policies have almost zero effects. The merchants of Ipiales stand out for the good attention, while the businesses of Tulcán consider as a differential element to the reliability.
Keywords: Tulcan; Ipiales; exchange rate; government policies; commercial premises